2010
DOI: 10.1088/1742-5468/2010/05/p05001
|View full text |Cite
|
Sign up to set email alerts
|

Statistical laws in urban mobility from microscopic GPS data in the area of Florence

Abstract: The application of Statistical Physics to social systems is mainly related to the search for macroscopic laws, that can be derived from experimental data averaged in time or space,assuming the system in a steady state. One of the major goals would be to find a connection between the statistical laws to the microscopic properties: for example to understand the nature of the microscopic interactions or to point out the existence of interaction networks. The probability theory suggests the existence of few classe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 10 publications
10
100
0
Order By: Relevance
“…They also identify vehicle stop positions and discover single trip length distribution deviates from an exponential and favors a power law gradually when trip length becomes longer. In summary, the results of urban mobility in [13] and [11] are consistent with ours. Thus, it can be conjectured that the phenomenon may not happen accidentally and exist in urban areas of cities widely.…”
Section: Displacementsupporting
confidence: 91%
See 1 more Smart Citation
“…They also identify vehicle stop positions and discover single trip length distribution deviates from an exponential and favors a power law gradually when trip length becomes longer. In summary, the results of urban mobility in [13] and [11] are consistent with ours. Thus, it can be conjectured that the phenomenon may not happen accidentally and exist in urban areas of cities widely.…”
Section: Displacementsupporting
confidence: 91%
“…Similar results are also discovered from GPS trackings [9,2,10,11,12,13], wireless network traces [14], check-ins from locationbased services [15,16] and even movements of banking notes [17].…”
Section: Introductionsupporting
confidence: 74%
“…9(b) we show the spatial distribution of the daily individual mobility derived from GPS private car data: the straight line in a logarithmic scale implies an exponential decay with the length that reminds us of the statistical Boltzmanns distribution. The results shed lights on the average traffic properties in a city, but future microscopic data will allow us to study the evolution of transient states from a microscopic (individual) point of view [10]. This also opens new research opportunities that use microscopic mobility data as a paradigm to study the human decision mechanisms and the information based interactions.…”
Section: New Tools For the Governance Of Mobility Demandmentioning
confidence: 94%
“…Recent studies [46,262] used GPS data of private vehicles for the city of Florence (Italy). and have shown that the total daily length trip is exponentially distributed (see Fig.…”
Section: Distribution Of the Trip Duration And Lengthmentioning
confidence: 99%